Theoretical interpretations of photoelectron spectra of platinum atom, its cation and anion. (January 2023) - Barysz, Maria; Syrocki, Łukasz
Highlights: First complete and accurate theoretical description of the energy levels of the neutral platinum atom and its positive, and negative ions have been shown. The calculated IOTC CASSCF/CASPT2 RASSI electronic affinity for platinum atom of 2.104 eV is one of the best theoretical values calculated so far. Our research shows that the order of the third and fourth ( 3 D 2 and 1 S 0 ) excited levels of the platinum atom may be different from that predicted by experiment. Results of the two-component relativistic methods showed that the eight-order DKH8 converge to the values of the infinite order IOTC method, which proves the high accuracy of both approaches. Abstract: Results of theoretical research on the ground and excited states of the platinum atom, its Pt − anion, and Pt + cation are presented. Calculations were carried out using the four-component multi-configuration Dirac-Hartree-Fock method with the spin-free relativistic eight-order Douglas-Kroll-Hess method, and the infinite order two-component method at high correlated level. The spin-orbit (SO) coupling is introduced via the restricted active space state interaction method with the use of the atomic mean field SO integrals. The results are interpreted in comparison with the experimental data. The theoretical analysis suggests different assignments and interpretations of some atomic and ionic states, and existence of three anionic bound states. The obtained electron affinity to Pt − 5 d 9 6 s 2 2 D 5 / 2 ground state is 2.104 eV (experimental value is 2.125 eV) which can be considered as very accurate result. The photodetachment Pt − 1 to Pt 0 spectra is provided. A comparative analysis of the accuracy of two-component methods is also presented.